The initial experience of MRI-guided precision prone breast irradiation with daily adaptive planning in treating early stage breast cancer patients - Ng, John; Pennell, Ryan; Formenti, Silvia C. (Frontiers in Oncology, 2022)
Background: A major challenge in breast radiotherapy is accurately targeting the surgical cavity volume. Application of the emerging MRI-guided radiotherapy (MRgRT) technique in breast radiotherapy may enable more accurate targeting and potentially reduce side effects associated with treatment. Purpose: To study the feasibility of delivering MRI-guided partial breast radiotherapy or Precision Prone Irradiation (PPI) to treat DCIS and early stage breast cancer patients. Materials and Methods: Eleven patients with diagnosed DCIS or early stage breast cancer treated with lumpectomy underwent CT-based and MRI-based simulations and treatment planning in the prone position. MRI-guided radiotherapy was utilized to deliver partial breast irradiation. A customized adaptive plan was created for each delivered radiotherapy fraction and the cumulative doses to the target volumes and nearby organs at risk were determined. The CT-based and the MRI-guided radiotherapy plans were compared with respect to target volumes, target volume coverage, and dose to nearby organs. Results: All patients receiving PPI successfully completed their treatments as planned. Clinical target volume (CTV) and planning target volume (PTV) dose coverage and organs-at-risk (OAR) dose constraints were met in all fractions planned and delivered and the MRI-guided clinical target volumes were smaller when compared to those of the CT-based partial breast radiotherapy plans for these eleven patients. Conclusions: MRI-guided partial breast radiotherapy as a breast radiotherapy technology is feasible and is a potential high clinical impact application of MRgRT. PPI has the potential to improve the therapeutic index of breast radiotherapy by more accurately delivering radiation dose to the cavity target and decreasing toxicities associated with radiation to the surrounding normal tissues. Prospective clinical data and further technical refinements of this novel technology may broaden its clinical implementation.